Diversity of antimicrobial resistance, stress resistance, and virulence factors of Salmonella, Shiga toxin-producing Escherichia coli, and Listeria monocytogenes from produce, spices, and tree nuts by whole genome sequencing - Hu, Lijun; Brown, Eric W.; Zhang, Guodong (Frontiers in Sustainable Food Systems, 2023)
The objective of this study was to analyze antimicrobial resistance (AMR), stress resistance, and virulence factors through whole genome sequencing (WGS) of 192 isolates that comprising 164 Salmonella isolates, 8 non-O157 Shiga toxin-producing Escherichia coli (STEC) isolates, and 20 Listeria monocytogenes isolates). These isolates were sourced from a national survey conducted between 2010 and 2017, involving 31,322 samples of produce (31 isolates), nuts (43 isolates), and spices (118 isolates). The findings yielded several key insights: 1) Within all Salmonella isolates studied, the most prevalent Salmonella serotypes included Give, Kentucky, Senftenberg, Mbandaka, Anatum, Newport, and Weltevreden. 2) All eight non-O157 STEC isolates were found to carry the genes blaEC, acrF, and mdtM, while all 20 L. monocytogenes isolates possessed fosX and lin genes. The Salmonella isolates displayed diverse AMR gene profiles, with 3.65% exhibiting multi-drug resistance. 3) Both Salmonella and non-O157 STEC isolates were discovered to carry stress genes associated with acid resistance, but none of L. monocytogenes isolates that carried acid-resistance gene. Salmonella isolates were found to carry multiple metal-resistance genes. The non-O157 STEC isolates universally exhibited acid-resistance genes, and four out of the 20 L. monocytogenes isolates were equipped with resistance genes against biocides. 4) 100% STEC isolates carried stx1 and stx2 genes, while none of them carried eae and wyz genes. Most L. monocytogenes isolates were found to contain 29 virulence genes and one pathogenicity island. All Salmonella isolates carried SPI-9, but lacked SPI-7, SPI-10, SPI-11, SPI-12, mig-5, prefA, tviA, and viaB genes. These findings on AMR, stress resistance, and virulence factors among the investigated isolates highlighted the potential risks they pose to public health, and provided the scientific foundation for the development of preventative and control strategies and guidance pertaining to these major foodborne pathogens.